From Reluctance to Fluency: Exploring Speaking Confidence through Digital Storytelling in Low-Motivated EFL Learners - Sulistianingsih, Endang; Fitriati, Sri Wuli; Mujiyanto, Januarius (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Speaking fluency and confidence remain a persistent challenge for Indonesian EFL learners, especially at low motivation and high language anxiety. Classroom strategies of the traditional type that pay attention to grammar accuracy can scarcely help students engage in genuine oral communication. This study investigated whether digital storytelling (DST) could be beneficial for low-motivated undergraduates in improving their speaking fluency and confidence. Defensible based on both Constructivist Learning Theory and Self-Determination Theory, the sample of the study was 19 participants of a private college in Central Java, Indonesia, who received a one-group pre-test–post-test. Across 6 weeks, students participated in DST processes such as script writing, voice recording, multimedia editing, and peer work. Data were obtained by speaking performance rubrics and a 5-point Likert scale on speaking confidence. It was found that the responses to both fluency (mean gain of 0.70) and confidence (mean gain of 1.06) were significantly improved with statistical significance (p < 0.001). The findings suggest that DST offers learners a safe, emotionally involving space to work on oral communication and to appropriate and internalize (subconsciously or reflexively) autonomy, emotional ownership, and motivational mechanisms. This research joins the rising volumes of work on digital pedagogy in EFL, focusing on the potential of DST for students who are hesitant to speak. Pedagogical implications for speaking, teaching, and technology use are then provided.